2012
DOI: 10.9790/1684-0233844
|View full text |Cite
|
Sign up to set email alerts
|

Turbocharging With Air Conditioner Assisted Intercooler

Abstract: ABSTRACT:The objective of a turbocharger is to improve an engine's volumetric efficiency by increasing the density of the intake gas (usually air, entering

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…As pointed out in the study of Muuqem in 2012, volumetric efficiency increases as the density of the air taken into the cylinder increases by the turbocharger [5]. As can be seen in Figure 5 in the study, it was observed that volumetric efficiency increases with turbocharged feeding.…”
Section: Fig 5 Volumetric Efficiencysupporting
confidence: 57%
See 2 more Smart Citations
“…As pointed out in the study of Muuqem in 2012, volumetric efficiency increases as the density of the air taken into the cylinder increases by the turbocharger [5]. As can be seen in Figure 5 in the study, it was observed that volumetric efficiency increases with turbocharged feeding.…”
Section: Fig 5 Volumetric Efficiencysupporting
confidence: 57%
“…The turbocharger technology uses an intercooler to cool the intake air. The aim is to bring the temperature of the air sucked as close to the ambient temperature as possible [5]. The temperature data shown in Figure 3, measured for three cycles during the turbocharged experiment, were observed quite close to the ambient temperature.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…If the exhaust gas pressure is high, it results in a high speed operation of turbo coupled with the compressor. Thus, a huge mass of air at high pressure gets into the intake manifold, increasing the volumetric efficiency and evaporation of fuel [47,48]. Increasing the intake boost pressure shortens the ignition delay [49].…”
Section: Super Charging or Turbo Chargingmentioning
confidence: 99%
“…If the exact value of intercooler pressure loss is available, the compressor pressure ratio will be calculated more accurately, but, if the pressure loss of the intercooler is not specified, it can be approximated to a value of 1.0 psi (Mohd 2012;Djemel et al 2017). Although pressure loss value can vary depending on shape and size of the intercooler, this value represents about the average amount used in this code.…”
Section: Required Parameters To Use Mapsmentioning
confidence: 99%